2009
DOI: 10.1101/gr.084640.108
|View full text |Cite
|
Sign up to set email alerts
|

Evolution under canalization and the dual roles of microRNAs—A hypothesis

Abstract: Canalization refers to the process by which phenotypes are stabilized within species. Evolution by natural selection can proceed efficiently only when phenotypes are canalized. The existence and identity of canalizing genes have thus been an important, but controversial topic. Recent evidence has increasingly hinted that microRNAs may be involved in canalizing gene expression. Their paradoxical properties (e.g., strongly conserved but functionally dispensable) suggest unconventional regulatory roles. We synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
167
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(179 citation statements)
references
References 89 publications
(120 reference statements)
10
167
0
2
Order By: Relevance
“…In addition to the measurement errors, the feedback loops and other systems motifs would often interfere with the miRNA-target interactions. Previous studies (Karres et al 2007;Wu et al 2009;Tang et al 2010) …”
Section: Validation Of Clip-identified Binding Sites By Expression Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the measurement errors, the feedback loops and other systems motifs would often interfere with the miRNA-target interactions. Previous studies (Karres et al 2007;Wu et al 2009;Tang et al 2010) …”
Section: Validation Of Clip-identified Binding Sites By Expression Assaymentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of endogenous small RNAs (;22 nt) that play an important role in the gene regulatory system (He and Hannon 2004;Stark et al 2005;Bushati and Cohen 2007;Flynt and Lai 2008;Wu et al 2009;Aqeilan et al 2010). A typical miRNA binds to the complementary sequences on target mRNAs, resulting in translational repression or target degradation (Bartel 2009).…”
mentioning
confidence: 99%
“…In fact, 30% of the transcriptome is regulated by miRNAs, and 25% of miRNA recognition elements between human and mouse is highly conserved (16,17,37). We used prediction algorithm in TargetScan to mine the 3ЈUTR of IGF-1R mRNA for the miRNA recognition element.…”
Section: Reduced Mir-214 Levels Correlate With High Igf-1rmentioning
confidence: 99%
“…Genome-scale analyses revealed that feedback and feedforward loops that contain miRNAs are also recurrent network motifs in large gene networks (Tsang et al, 2007;Martinez et al, 2008;Re et al, 2009), so that miRNAs can provide biological robustness by participating in these loops (Hornstein and Shomron, 2006;Wu et al, 2009a;Herranz and Cohen, 2010;Osella et al, 2011;Pelaez and Carthew, 2012). miRNAs are small (approximately 22 nucleotides) noncoding single-stranded RNAs that regulate gene expression post-transcriptionally.…”
Section: Mirna-containing Circuits Contribute To the Robustness Of Bimentioning
confidence: 99%
“…Feedforward loops can confer robustness through different mechanisms. They can buffer the impact of noise on target gene expression, contributing to enhance the robustness of the network Hornstein and Shomron, 2006;Wu et al, 2009a;Osella et al, 2011). In an incoherent feedforward loop, fluctuations of the upstream factor are uncoupled from the final output of the target gene, because the intermediate component of the indirect path of the loop will compensate changes in the input signal (Ebert and Sharp, 2012).…”
mentioning
confidence: 99%